Binding mechanism of lipase with Lentinus edodes mycelia polysaccharide by multi‐spectroscopic methods. Issue 2 (17th December 2021) - Liu, Jianli; Chen, Jiahe; Liu, Xiangyang; Shao, Wei; Mei, Xueying; Tang, Zhipeng; Cao, Xiangyu
Abstract: It is an effective strategy to avoid obesity by inhibiting the activity of lipase. In this study, the binding mechanism of lipase and Lentinus edodes mycelia polysaccharide (LMP) were explored with multi‐spectral methods, for example, three‐dimensional (3D) fluorescence, Fourier‐transformed infrared (FT‐IR), and Raman spectra. At 290 K, the binding constant was 2.44 × 10 5  L/mol, there was only one binding site between LMP and lipase. Static quenching was the quenching mechanism. The major forces were hydrogen bonding and van der Waals force. The binding of LMP to lipase impacted the microenvironment around tyrosine and tryptophan residues. The polarity around these residues was decreased and hydrophobicity was enhanced. This study not only revealed the binding mechanism of LMP on lipase but also provided scientific evidence for expanding the application of LMP in functional food industries. Abstract : A polysaccharide from Lentinus edodes Mycelia bound with lipase by one binding site. The binding was spontaneous and changed the lipase secondary structure.